MODELING OF TRANSFORMATION FEATURES FOR NITROGEN AND PHOSPHORUS COMPOUNDS IN THE CONDITIONS OF THE NOVOSIBIRSK RESERVOIR - Aleksandr A. Tskhai; Vladislav Y. Ageikov; Aleksandr N. Semchukov (Водное хозяйство России: проблемы, технологии, управление)
The article presents a model description of spatially inhomogeneous features for the ecosystem of the Novosibirsk reservoir, the largest in Western Siberia, based on the reproduction of biogeochemical cycles of limiting elements. We have formulated the model tool set for studying quantitative and qualitative changes in the state variables of water bio/geo/cenosis. To obtain an adequate picture of environmental processes occurring in various parts of the reservoir modeling of the transformation features of nitrogen and phosphorus compounds in the waters of the Novosibirsk reservoir was performed in the box approximation. Phytoplankton biomass in a relatively shallow water area significantly exceeds concentrations in the deep-water and near-dam parts of the reservoir. A detailed by maximum permissible values, in the water areas of the reservoir is reproduced. The estimates obtained during the simulation generally correspond to the observed data. This study can serve as a basis for developing a model approach to monitoring and management of ecosystem processes in the Novosibirsk reservoir.